Uganda : Fourth Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria: Staff Report; Staff Supplement; Press Release. (IMF Staff Country Reports; Country Report ;, 2012)
The Fourth Review Under the Policy Support Instrument (PSI) for Uganda highlights that the PSI-supported program is on track. All end-December 2011 quantitative assessment criteria were met, as were most of the structural benchmarks. The stance of macroeconomic policy remains appropriate. Monetary tightening, initiated in July 2011 in response to rising inflation, has been effective in reducing demand and price pressures in the economy. High interest rates supported by tighter fiscal policy have strengthened the currency and raised reserve levels.